2019
DOI: 10.4162/nrp.2019.13.1.23
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with anemia among female adult vegetarians in Malaysia

Abstract: BACKGROUND/OBJECTIVESA large number of studies on anemia have focused mostly on pregnant women or children. The vegetarian population, which is another potential risk group for anemia, remains largely unexplored. Therefore, this cross-sectional study examined the associations of the sociodemographic, lifestyle, nutritional, and psychological factors with the anemia status among female adult vegetarians.SUBJECTS/METHODSA total of 177 female vegetarians were recruited from a Buddhist and Hindu organization in Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…As presented in Table 2, the majority of the included studies ( n = 20, 86%) were published after 2012. Eighteen out of 23 (78%) were cross‐sectional studies (Baines et al, 2007; Beezhold et al, 2010; Chai et al, 2019; Forestell & Nezlek, 2018; Hessler‐Kaufmann et al, 2021; Hibbeln et al, 2018; Hosseinzadeh et al, 2016; Jin et al, 2021; Kapoor et al, 2017; Lavallee et al, 2019; Li et al, 2019; Matta et al, 2018; Meesters et al, 2016; Michalak et al, 2012; Northstone et al, 2018; Norwood et al, 2019; Paslakis et al, 2020; Zamani et al, 2020), three (13%) were cohort studies (Link et al, 2008; Sánchez‐Villegas et al, 2015; Shen et al, 2021), and the remaining two (9%) were RCTs (Agarwal et al, 2015; Beezhold & Johnston, 2012). Six studies were conducted in Europe (Hibbeln et al, 2018; Matta et al, 2018; Meesters et al, 2016; Michalak et al, 2012; Northstone et al, 2018; Sánchez‐Villegas et al, 2015), another six in the US (Agarwal et al, 2015; Beezhold & Johnston, 2012; Beezhold et al, 2010; Forestell & Nezlek, 2018; Jin et al, 2021; Link et al, 2008), two were conducted in Australia (Baines et al, 2007; Norwood et al, 2019), four in Asia (Chai et al, 2019; Hosseinzadeh et al, 2016; Kapoor et al, 2017; Li et al, 2019), and one study combined Europe, Asia and America (a grouping of populations from Germany, Russia, China and the US) (Lavallee et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As presented in Table 2, the majority of the included studies ( n = 20, 86%) were published after 2012. Eighteen out of 23 (78%) were cross‐sectional studies (Baines et al, 2007; Beezhold et al, 2010; Chai et al, 2019; Forestell & Nezlek, 2018; Hessler‐Kaufmann et al, 2021; Hibbeln et al, 2018; Hosseinzadeh et al, 2016; Jin et al, 2021; Kapoor et al, 2017; Lavallee et al, 2019; Li et al, 2019; Matta et al, 2018; Meesters et al, 2016; Michalak et al, 2012; Northstone et al, 2018; Norwood et al, 2019; Paslakis et al, 2020; Zamani et al, 2020), three (13%) were cohort studies (Link et al, 2008; Sánchez‐Villegas et al, 2015; Shen et al, 2021), and the remaining two (9%) were RCTs (Agarwal et al, 2015; Beezhold & Johnston, 2012). Six studies were conducted in Europe (Hibbeln et al, 2018; Matta et al, 2018; Meesters et al, 2016; Michalak et al, 2012; Northstone et al, 2018; Sánchez‐Villegas et al, 2015), another six in the US (Agarwal et al, 2015; Beezhold & Johnston, 2012; Beezhold et al, 2010; Forestell & Nezlek, 2018; Jin et al, 2021; Link et al, 2008), two were conducted in Australia (Baines et al, 2007; Norwood et al, 2019), four in Asia (Chai et al, 2019; Hosseinzadeh et al, 2016; Kapoor et al, 2017; Li et al, 2019), and one study combined Europe, Asia and America (a grouping of populations from Germany, Russia, China and the US) (Lavallee et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, nine cross‐sectional studies found that adherence to vegetarian diets was associated with an increased risk of depression (Baines et al, 2007; Forestell & Nezlek, 2018; Hibbeln et al, 2018; Kapoor et al, 2017; Li et al, 2019; Matta et al, 2018; Meesters et al, 2016; Michalak et al, 2012; Norwood et al, 2019). Five cross‐sectional studies assessing the relationship between a vegetarian diet and depression found no association between the two (Chai et al, 2019; Hessler‐Kaufmann et al, 2021; Lavallee et al, 2019; Northstone et al, 2018; Paslakis et al, 2020). The Lavallee et al (2019) study, however, found no association between vegetarianism and depression in the US, German and Russian representative samples or in German student samples but found that vegetarianism was related to slight increases over time in anxiety and depression in Chinese students (Lavallee et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly evident in Indian ethnicity, exposing Indian women to a higher risk of developing iron-deficiency anemia during pregnancy [ 43 – 45 ]. This could be due to the common practices of vegetarian diet among Indians who do not receive adequate iron-rich foods in their meals [ 46 ]. Poverty, low education, and lack of iron-rich sources in food intake are often regarded as reasons to poor dietary intake of iron among women in developing nations [ 41 , 45 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%